2017
DOI: 10.3389/fpls.2017.01497
|View full text |Cite
|
Sign up to set email alerts
|

Mycorrhizal Associations and Trophic Modes in Coexisting Orchids: An Ecological Continuum between Auto- and Mixotrophy

Abstract: Two distinct nutritional syndromes have been described in temperate green orchids. Most orchids form mycorrhizas with rhizoctonia fungi and are considered autotrophic. Some orchids, however, associate with fungi that simultaneously form ectomycorrhizas with surrounding trees and derive their carbon from these fungi. This evolutionarily derived condition has been called mixotrophy or partial mycoheterotrophy and is characterized by 13C enrichment and high N content. Although it has been suggested that the two m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 69 publications
1
52
0
1
Order By: Relevance
“…After the pioneering work of Gebauer and Meyer () and Trudell et al (), many studies have applied stable isotope analyses to assess the trophic modes of plants (e.g. Bidartondo, Burghardt, Gebauer, Bruns, & Read, ; Abadie et al, ; Tedersoo, Pellet, Kõljalg, & Selosse, ; Zimmer et al, ; Hynson, Preiss, Gebauer, & Bruns, ; Johansson, Mikusinska, Ekblad, & Eriksson, ; Hynson, Schiebold, & Gebauer, ; Jacquemyn, Waud, et al, ). Bidartondo et al (), for example, analysed isotope signatures in several orchid species inhabiting forest habitats and showed that orchids that associated primarily with rhizoctonia fungi were not significantly enriched in 13 C, whereas orchids associated with ectomycorrhizal fungi showed both significant enrichment in 13 C and 15 N. Similarly, Hynson et al () showed evidence for mycoheterotrophy on ectomycorrhizal fungi in several species of the tribe Pyroleae.…”
Section: Trophic Modes: a Continuum From Autotrophy To Mycoheterotrophy?mentioning
confidence: 99%
See 3 more Smart Citations
“…After the pioneering work of Gebauer and Meyer () and Trudell et al (), many studies have applied stable isotope analyses to assess the trophic modes of plants (e.g. Bidartondo, Burghardt, Gebauer, Bruns, & Read, ; Abadie et al, ; Tedersoo, Pellet, Kõljalg, & Selosse, ; Zimmer et al, ; Hynson, Preiss, Gebauer, & Bruns, ; Johansson, Mikusinska, Ekblad, & Eriksson, ; Hynson, Schiebold, & Gebauer, ; Jacquemyn, Waud, et al, ). Bidartondo et al (), for example, analysed isotope signatures in several orchid species inhabiting forest habitats and showed that orchids that associated primarily with rhizoctonia fungi were not significantly enriched in 13 C, whereas orchids associated with ectomycorrhizal fungi showed both significant enrichment in 13 C and 15 N. Similarly, Hynson et al () showed evidence for mycoheterotrophy on ectomycorrhizal fungi in several species of the tribe Pyroleae.…”
Section: Trophic Modes: a Continuum From Autotrophy To Mycoheterotrophy?mentioning
confidence: 99%
“…However, the assumed autotrophy of rhizoctonia‐associated orchid species has recently been challenged (Gebauer et al, ; Schiebold et al, ; Schweiger et al, ). Moreover, detailed molecular analyses using high‐throughput sequencing techniques have shown that many so‐called ‘rhizoctonia‐associated’ species also associate with ectomycorrhizal fungi and vice versa (Jacquemyn et al, ; Jacquemyn, Brys, Waud, Busschaert, & Lievens, ; Jacquemyn, Waud, et al, ), indicating that a strict distinction between rhizoctonia‐associated and ectomycorrhiza‐associated species cannot be maintained, neither based on their stable isotope signatures nor their mycorrhizal communities. Similar results have been observed in other genera displaying autotrophy and mycoheterotrophy.…”
Section: Partner Selectivity and Niche Breadthmentioning
confidence: 99%
See 2 more Smart Citations
“…S spiralis and S. novae‐zelandiae ; Frericks, Munkacsi, Ritchie, Luo, & Lehnebach, ; Tondello et al., ). Indeed, a recent study showed that this primer pair was able to detect a large number of Tulasnellaceae OTUs in typical rhizoctonia associated orchids ( Dactylorhiza fuchsii and D. incarnata ) (Jacquemyn, Waud, et al., ). Therefore, our results should reflect the overall influence of latitude and longitude on OMF diversity in S. spiralis .…”
Section: Discussionmentioning
confidence: 99%